OPERATING GUIDELINES for the Sustainable Development Working Group. - Sustainable Development Working Group (SDWG) (Sustainable Development Working Group (SDWG), 2014)
Operating guidelines of the Arctic Council working group Sustainable Development Working Group (SDWG), submitted to the Senior Arctic Officials meeting in Yellowknife, Canada, October 22-23 2014. NOTE: The operating guidelines as presented in this document have not been finally adopted, and should therefore not be viewed as the final version of the operating guidelines.